Hello neighbour : formative and summative assessment using Web 2.0 tools workshop in Politeknik Seberang Perai / Muhammad Aiman Abdul Halim and Noor Azli Affendy Lee - Abdul Halim, Muhammad Aiman; Affendy Lee, Noor Azli (Academy of Language Studies, 2022)
Muhammad Yunus, a Bangladeshi Nobel Peace Prize winner had once said: “A university should not be an island where academics attain higher and higher levels of knowledge without sharing any of this knowledge with its neighbours.” Following this notion, three lecturers from UiTM Cawangan Pulau Pinang (UiTMCPP) went to our tertiary education neighbour, Politeknik Seberang Perai on 4th August 2022 to share some of their insights and experiences. Assoc. Prof. Ir. Dr. Zakaria Hussain from Pengajian Kejuruteraan Elektrik (PKE), Mr. Noor Azli Affendy Lee and Mr. Muhammad Aiman Abdul Halim from Akademi Pengajian Bahasa (APB) UiTMCPP were invited by Jabatan Pengajian Am, Politeknik Seberang Perai to conduct a 6-hour hands-on workshop focusing on the application of Web 2.0 tools for assessment in higher education. The workshop was conducted at Language Lab 1, Politeknik Seberang Perai and was attended by around 30 lecturers from Unit Bahasa Inggeris and Unit Pengajian Islam.